Electrocatalytic and Photocatalytic Reduction of CO2 to CO by Cobalt(II) Tripodal Complexes: Low Overpotentials, High Efficiency and Selectivity - Wang, Jia‐Wei; Huang, Hai‐Hua; Sun, Jia‐Kai; Ouyang, Ting; Zhong, Di‐Chang; Lu, Tong‐Bu (ChemSusChem, 2018)
The reduction of carbon dioxide (CO2) has been considered as an approach to mitigate global warming and to provide renewable carbon‐based fuels. Rational design of efficient, selective, and inexpensive catalysts with low overpotentials is urgently desired. In this study, four cobalt(II) tripodal complexes are tested as catalysts for CO2 reduction to CO in a MeCN/H2O (4:1 v/v) solution. The replacement of pyridyl groups in the ligands with less basic quinolinyl groups greatly reduces the required overpotential for CO2‐to‐CO conversion down to 200–380 mV. Benefitting from the low overpotentials, a photocatalyst system for CO2‐to‐CO conversion is successfully constructed, with an maximum turnover number (TON) of 10 650±750, a turnover frequency (TOF) of 1150±80 h−1, and almost 100 % selectivity to CO. These outstanding catalytic performances are further elucidated by DFT calculations. Electric/light orchestration: Four cobalt complexes with tripodal ligands are utilized as high‐performance molecular electro‐ and photocatalysts for the reduction of CO2 to CO in a water‐containing system. By the introduction of less basic aromatic nitrogen donors in the tripodal ligands, the overpotentials can be reduced down to record low values of 200–380 mV, leading to high efficiency and selectivity for photocatalytic reduction of CO2 to CO.